2018
DOI: 10.1111/ijsa.12203
|View full text |Cite
|
Sign up to set email alerts
|

Affective responses to abuse in the workplace: The role of hope and affective commitment

Abstract: Affective responses constitute the mechanism by which abusive supervision received is associated with subordinates' turnover intentions. Using affective events theory (AET) as a theoretical framework, we suggest that abusive supervision is a contextual event that is associated with subordinates' affective reactions and corresponding evaluative judgment of their workplace, which ultimately leads to increased turnover intentions, a prominent withdrawal outcome. We examine two affective responses as mediators, ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 54 publications
2
52
0
Order By: Relevance
“…Employees are dissatisfied with unreasonable role ambiguity, conflict, and overload, which then triggers negative affect. Employees experiencing negative affect are inclined to express it through CWB in an attempt to eliminate the negative affect (Rodell & Judge, ; Tillman, Gonzalz, Crawford, & Lawrence, ; Yang & Diefendorff, ). In sum, we hypothesize:…”
Section: Theory and Hypothesismentioning
confidence: 99%
“…Employees are dissatisfied with unreasonable role ambiguity, conflict, and overload, which then triggers negative affect. Employees experiencing negative affect are inclined to express it through CWB in an attempt to eliminate the negative affect (Rodell & Judge, ; Tillman, Gonzalz, Crawford, & Lawrence, ; Yang & Diefendorff, ). In sum, we hypothesize:…”
Section: Theory and Hypothesismentioning
confidence: 99%
“…It was argued that supervisor support increases employee's organizational commitment [17]. It was found that supervisor-subordinate relationship affects organizational commitment [34]. It was argued that organizational support in the form of support K. Bodjrenou et al…”
Section: Organizational Supportmentioning
confidence: 99%
“…from the supervisor positively associates generally with affective commitment [14]. Based on affective events theory (AET), it has been observed that the affective commitment of a subordinate who has experienced abuse from a supervisor is likely to decrease and this employee may in turn leave the organization [34]. A group of scholars found that effective direct supervision contribute to increase an employee's commitment to an organization, more specifically his or her affective commitment [18].…”
Section: Organizational Supportmentioning
confidence: 99%
“…The facets of CWB included property destruction, inappropriate verbal actions, inappropriate physical actions, poor attendance, poor quality work, unsafe behavior, theft and related behavior, misuse of information, misuse of time and resources, alcohol use, and drug use. Focusing on victims of CWB, Tillman, Gonzalez, Crawford, and Lawrence (, this issue) highlighted the affective reactions to abusive supervision.…”
Section: Forms Of Cwb: New and Diversementioning
confidence: 99%
“…Through their multimeasure, time‐lagged design, Mercado and Dilchert provided evidence that employees who experience family responsibilities interfering with their work perform more CWB (and display lower citizenship behaviors) than those who do not experience family–work interference. Tillman et al (, this issue) showed that individuals who are subjected to abusive supervision experience hopelessness and reduced affective commitment, and express higher intent to leave their organizations.…”
Section: Determinants Of Cwbmentioning
confidence: 99%